A Productive time in modern organizations: Contributions of Psychology - Solf Zárate, Arturo (2017)
The main contributions of psychology within the context of a more efficient use of time by workers in the execution of their duties are hereby presented. First, a theoretical framework is included touching upon: climate and culture, personality, chronotype, procrastination, cyberslacking. The second part deals with certain psychological interventions aimed at fostering a more rational use of time.